(untitled) (UNED Research Journal, 2019)
Air quality in this country surpasses levels accepted by the World Health Organization. A mitigation effort in regards to these gases is sustainable transportation, with a significant reduction in emissions by this sector. Costa Rica is currently moving towards a zero-emission automobile fleet, with electric cars. In this article I discuss the possibilities for Costa Rica to electrify its public bus fleet, in particular electric buses and hydrogen cells, and compare it with other international experiences.